DESIMAL BERULANG UNTUK SUATU NUMERATOR - Affaf, Moh. (Penerbit STKIP PGRI Bangkalan, 2018)
Let denote a positive integer relatively prime to 10 and m be natural number less than n and relatively prime to n. Let the period of be m/n with ab > 1. Break the  repeating block of ab digits up into b sub blocks, each of length a, and let